DETERMINAN EKSPOR LADA INDONESIA PERIODE 2009-2019: STUDI KASUS 10 MITRA DAGANG - Reginald, Indigo Caniggia; Iswan Noor (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
One of the flagship commodities with great potential for Indonesia's economic growth is black pepper (Piper nigrum L). The importance of maintaining Indonesia's competitiveness in black pepper exports, both in the domestic and international markets, has increased in tandem with the rising export volume, with the primary determinant of its competitiveness being the demand for black pepper. Data from the 2021 plantation balance sheet recorded black pepper exports at 39,961.36 tons and black pepper imports at 295.37 tons, while tea exports reached 46,003.88 tons with tea imports at 10,442.75 tons. This research aims to analyze the influence of factors such as Gross Domestic Product (GDP), exchange rate, tariffs, and distance on Indonesian black pepper exports, adopting a research model similar to the one used by Shepotylo (2012), which utilizes econometric modeling, with a quantitative and descriptive analysis approach. The research results indicate that the Gross Domestic Product variable has a negative and significant impact on Export Value, with a probability value of t < 0.05, indicating a significant influence. On the other hand, the Exchange Rate and Tariff variables have a negative but non-significant impact on Export Value, with a probability value of t > 0.05, indicating their lack of significance. Furthermore, the research findings also reveal that the Distance variable has a significant negative impact on Export Value, with a probability value of t < 0.05, indicating a significant influence.